The efficacy of the TEACH e-Learning course at improving early childhood educators' physical activity and sedentary behaviour self-efficacy, knowledge, intentions, and perceived behavioural control: a randomized controlled trial - Matthew Bourke; Brianne A. Bruijns; Leigh M. Vanderloo; Jennifer Irwin; Rachel Heydon; Valerie Carson; Patti-Jean Naylor; Andrew M. Johnson; Kristi B. Adamo; Shauna M. Burke; Brian W. Timmons; Patricia Tucker (BMC, 2024)
Abstract Background Early childhood educators play a critical role in promoting physical activity and reducing sedentary time in childcare centres. However, early childhood educators receive limited specialised pre- and in-service learning opportunities relating to these behaviours and may lack the capacity to effectively engage children in healthy movement behaviours. This study aimed to examine the efficacy of an e-Learning course on increasing early childhood educators' physical activity and sedentary behaviour-related capacities. Methods A two-group parallel randomized controlled trial was conducted with early childhood educators in Canada (Mage = 41.78, 97% female). Participants randomized to the intervention group were asked to complete a physical activity and sedentary behaviour e-Learning course within a 4-week period. Participants randomized to the waitlist control condition were assigned to a waitlist to receive the intervention after the testing period. Participants reported on their self-efficacy, knowledge, intentions, and perceived behavioural control relating to physical activity and sedentary behaviours at baseline, post-intervention, and 3 months follow-up. Linear mixed effects models were estimated to determine difference in changes in outcomes from baseline to post-intervention, and follow-up. Results A total of 209 early childhood educators participated in the study (intervention n = 98; control n = 111). The TEACH e-Learning course was found to be efficacious at improving all of the examined outcomes, with standardized effect sizes ranging from d = 0.58 to d = 0.65 for self-efficacy outcomes, d = 0.66 to d = 1.20 for knowledge outcomes, d = 0.50 to d = 0.65 for intention outcomes, and d = 0.33 to d = 0.69 for perceived behavioural control outcomes post-intervention. The intervention effects were sustained at follow-up for all outcomes apart from perceived behavioural control to limit screen time. Additionally, the magnitude of the effect for knowledge outcomes decreased at follow-up, with standardized effect sizes ranging from d = 0.49 to d = 0.67. Conclusions The e-Learning course was highly successful at improving early childhood educators' capacity pertaining to physical activity and sedentary behaviours. Providing training content through e-Learning may be an efficacious approach to providing continual professional learning opportunities relating to physical activity and sedentary time to early childhood educators on a large scale.